Mid-Pliocene restriction of the Indonesian Gateway and its implication on ocean circulation and climate - Karas, Cyrus (2010)
The impacts of the constrictions of the Indonesian Gateway and the Central American Seaway on ocean circulation are among the keys to understand Pliocene climate evolution, including the intensification of the Northern Hemisphere Glaciation between 3.5 and 2.5 Ma. Plate tectonic reconstructions show that the main reorganization of one such seaway, the Indonesian Gateway, occurred between 4 and 3 Myr ago. Model simulations have suggested that this tectonic reorganization triggered far-reaching effects on ocean circulation and climate, including a switch in the source of waters feeding the Indonesian Throughflow into the Indian Ocean. This PHD thesis aims to elucidade the climatic and oceanographic changes related to the constriciton of the Indonesian Gateway. It presents combined d18O and Mg/Ca ratios of planktonic foraminifera (marine protozoa) from surface and subsurface levels to reconstruct the thermal structure and changes in salinities at four following sensitive core sites in the Indian and Pacific Oceans from ~6 to 2 Myr ago: DSDP Site 214 in the tropical east Indian Ocean, ODP Site 709C in the west tropical Indian Ocean, ODP 763A in the subtropical east Indian Ocean under the influence of the Leeuwin Current, and DSDP Site 590B in the southwest Pacific Ocean at the Tasman Front: In the outflow region of the Indonesian Throughflow (DSDP Site 214), sea surface conditions remained relatively stable throughout the mentioned Pliocene interval, while subsurface waters (300-450 m water depth) freshened and cooled by about 4°C between 3.5 and 2.95 Myr ago. After 2.95 Ma, constantly low subsurface temperatures and fresher conditions suggested a prevailing throughflow of North Pacific source waters through the Indonesian Gateway. These findings supported the hypothesis of Cane and Molnar (2001) that the constriction of the Indonesian Gateway (4-3 Ma) led to a major reorganization in the Indonesian Throughflow. The cooling and shoaling of the thermocline in the tropical Indian Ocean might have contributed to ...